2006
DOI: 10.1159/000095873
|View full text |Cite
|
Sign up to set email alerts
|

Does Hepcidin Affect Erythropoiesis in Hemodialysis Patients?

Abstract: Introduction: Prohepcidin is the precursor of hepcidin, a liver-derived peptide involved in iron metabolism by blocking its intestinal absorption and its release by the reticuloendothelial system. Iron overload and inflammation increase hepcidin expression, whereas anemia and hypoxia suppress it. In the present study prohepcidin levels were determined in the serum of hemodialysis (HD) patients and its correlations with iron metabolism markers, C-reactive protein (CRP) and hematocrit (Hct) were assessed. Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 48 publications
(46 reference statements)
2
32
1
Order By: Relevance
“…In contrast, Malyszko et al [19] showed a positive association between prohepcidin and rHuEPO dose in the HD patients treated with rHuEPO. A negative association between prohepcidin and Hct but not with rHuEPO dose was also reported in a recent study [20]. …”
Section: Discussionsupporting
confidence: 77%
“…In contrast, Malyszko et al [19] showed a positive association between prohepcidin and rHuEPO dose in the HD patients treated with rHuEPO. A negative association between prohepcidin and Hct but not with rHuEPO dose was also reported in a recent study [20]. …”
Section: Discussionsupporting
confidence: 77%
“…13 Of note, our data are not entirely singular. 5,12,20 Similar inconsistencies are apparent in the literature as to the relationship between pro-hepcidin and hemoglobin/hematocrit levels: either inverse 13,21 or direct, positive correlations. 22 In contrast to these studies, we observed no signifi cant correlation between pro-hepcidin and hemoglobin even.…”
Section: Discussionmentioning
confidence: 80%
“…In a study done by (El Ftheriads et al, 2006) showed that prohepcidin level may be associated with the factors that inhibit erythropoiesis in hemodialysis patient. [15], [16] In a cross sectional study on 505 non dialysis CKD patient, not treated with parenteral iron. Hepcidin level was significantly increased according to CKD stage without any association with estimated GFR, in contrary hepcidin level was found to be negatively associated with hemoglobin concentration in high ferritin group.…”
Section: Resultsmentioning
confidence: 99%